KUALITAS PELAYANAN TERHADAP MINAT BELI KONSUMEN - Linda Darniati Zebua; Heseziduhu Lase; Martinus Telaumbanua; Yaatulo Warae; Ferdinand Tharorogo Wau; Sofumboro Ndruru (Universitas Nias Raya, 2023)
The purpose of this study is to find out the influence of service quality toword consumer buying interest in Toko Imelda Ponsel Telukdalam In South Nias. The type of research used is a quantitative type of causal nature. The data source is from consumers, with the population and sample in the study being as many as 40 people. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple linear regression analysis. The results of this study showed there is an influence on the quality of service toword consumer buying interest in Toko Imelda Ponsel Telukdalam in South Nias.